PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DAN TIPE TO STAY-TO STRAY TERHADAP HASIL BELAJAR SISWA KELAS X IPS SMAN 8 KOTA JAMBI - Zuhri Saputra Hutabarat, Suci Rahmadani, (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine (1) Student learning outcomes in economic subjects class X IPS SMAN 8 Jambi City by using cooperative learning models Think Talk Write type, (2) Student learning outcomes in economic subjects X class IPS SMAN 8 Jambi City with using the Cooperative Learning model Type To Stay - To Stray, (3) Comparison of student learning outcomes in economic subjects using the Cooperative Learning model Type Think Talk Write and To Stay To Stray. The results of this study indicate that (1) Student learning outcomes in economic subjects in class X IPS SMAN 8 Kota Jambi by using the cooperative learning model Think Talk Write type obtained an average nose (mean) of 81.48, (2) Student learning outcomes on economic subjects class X IPS SMAN 8 Jambi City using the Cooperative Learning model Type To Stay - To Stray obtained an average count of 76.02, (3) Comparison of student learning outcomes in economic subjects using the Learning model Cooperative Type of Think Talk Write and To Stay To Stray with Sig. 0,000 <0.05. Keywords : Think Talk Write, To Stay-To Stray